Academic Resilience and Religiosity Among College Students Facing Post-Pandemic Learning - Nuraliah Ali; Mardan Umar; Abdul Ziqron Mopoliu (IJORER : International Journal of Recent Educational Research, 2023)
Objective: The shock of rapid shifts in academic activity patterns affects students' mental health and academic progress. Resilience and religiosity in dealing with adversity are vital to surviving the post-pandemic transitional period. Method: This research is qualitative-quantitative descriptive with a combination of concurrent embedded methods, and the primary method is qualitative. Three hundred forty-one samples from 18,537 populations were taken using a simple random sampling technique with an error rate of 1.00% x 5.00%. Data was collected through an electronic questionnaire (G-Form). The instruments used were ARS-30 Cassidy and 4-BDRS Saroglou. Results: The results showed that students' academic resilience and religiosity were positive, with very high, high, and moderate scores and none in the low or shallow range. In all the religions studied resilient students are also religious. This shows that persistent children can describe events, adapt, and avoid negative emotional responses; they also have trust, determination, and faith in God. The implication is that when students face problems, risks, and academic difficulties in face-to-face learning during the post-pandemic transition period, they show the ability not to give up easily; they believe that God will help them through challenges and difficulties. Novelty: The novelty of the research is that good academic resilience and religiosity positively impact student’s academic activities.